Metabolic syndrome, adiposity, diet, and emotional eating are associated with oxidative stress in adolescents - Ramírez-Garza, Sonia L.; Laveriano-Santos, Emily P.; Moreno, Juan J.; Bodega, Patricia; de Cos-Gandoy, Amaya; de Miguel, Mercedes; Santos-Beneit, Gloria; Fernández-Alvira, Juan Miguel; Fernández-Jiménez, Rodrigo; Martínez-Gómez, Jesús; Ruiz-León, Ana María; Estruch, Ramon; et al. (Frontiers in Nutrition, 2023)
Background Metabolic syndrome (MS), a condition related to adiposity and oxidative stress, can develop in adolescence, a critical stage in life that impacts health in adulthood. However, there is scarce scientific research about the relationship between lifestyle factors, emotion management, and oxidative stress in this phase of life. Aim To analyze whether nutritional parameters, lifestyle factors, emotion management, and MS in adolescents are associated with oxidative stress measured by the biomarker 8-isoprostane. Methods A cross-sectional study was carried out in 132 adolescents (48.5% girls, aged 12 ± 0.48 years) and data were collected on nutritional parameters (anthropometric measurements, biochemical analyzes, and blood pressure), lifestyle factors (physical activity, sleep, and diet), and emotion management (self-esteem, emotional eating, and mood). 8-isoprostane was analyzed in spot urine samples. The study population was categorized in three groups (healthy, at-risk, and with MS) using the International Diabetes Federation definition of MS in adolescents. To capture more complex interactions, a multiple linear regression was used to analyze the association between 8-isoprostane and the aforementioned variables. Results Urinary 8-isoprostane levels were significantly higher in the MS group compared to the healthy group (1,280 ± 543 pg./mg vs. 950 ± 416 pg./mg respectively). In addition, univariable analysis revealed positive significant associations between 8-isoprostane and body mass index, waist circumference, waist-to-height ratio, body fat percentage, blood lipid profile and glucose, emotional eating, and refined cereal intake. Conversely, a negative significant association was found between 8-isoprostane and sleep duration and fish intake. The multiple linear regression analysis revealed associations between 8-isoprostane and LDL-c (β = 0.173 value of p = 0.049), emotional eating (low β = 0.443, value of p = 0.036; high β = 0.152, value of p = 0.470), refined cereal intake (β =0.191, value of p = 0.024), and fish intake (β = −0.187, value of p = 0.050). Conclusion The MS group, LDL-c, emotional eating, and high refined cereals and low fish intakes were associated with higher levels of oxidative stress in an adolescent population.